Choro pânico do mundo: a melancolia em Carlos Drummond de Andrade - Paulo Eduardo Bittencourt Gosling Fausto (2022)
This present essay intends to create a view about the poetry of Carlos Drummond de Andrade under the meaning of melancholy. Taken in this present work from an aesthetic point of view, that is, bringing the melancholic temperament into the compositions and figurations of poetry, it is relevant to observe how Drummond sees and deals with this feeling and, also, how he transfigures it in his books under the most different facets, from procedures that suggest a multiplicity of formal and thematic factors, but, of course, with a line of continuity that reveals a common thread to this vast and complex poetry. As a basis for these considerations, were taken three central poems to Drummond's work: “Poema de Sete Faces” (Alguma Poesia, 1930), “A Flor e a Náusea” (A Rosa do Povo, 1945) and “Relógio do Rosário” (Claro Enigma, 1951). The present dissertation aims at a detailed exploration of these poems, using the most diverse conceptual aspects as a basis of reference, especially those that are somehow related to the issue of melancholy, along with critical aspects of the vast bibliography on Carlos Drummond de Andrade and, yet, a wider selection of other poems from Drummond that aim to support the readings made of the selected central poems.